Comparison of GLUT-1, SGLT-1, and SGLT-2 expression in false-negative and true-positive lymph nodes during the 18F-FDG PET/CT mediastinal nodal staging of non-small cell lung cancer. (September 2018) - Taira, Naohiro; Atsumi, Eriko; Nakachi, Saori; Takamatsu, Reika; Yohena, Tomofumi; Kawasaki, Hidenori; Kawabata, Tsutomu; Yoshimi, Naoki
Highlights: Glucose metabolism can cause false negative mediastinal lymph nodes of NSCLC via 18 F-FDG PET/CT. We investigated the association between glucose transporters and mediastinal nodal status. GLUT-1 expression was associated with PET true-positive mediastinal lymph nodes. SGLT-2 expression was associated with PET false-negative mediastinal lymph nodes. There was no positive staining for SGLT-1 in both lymph node types. Abstract: Introduction: Although positron emission tomography (PET) with 2-deoxy-2-[fluorine-18]fluoro-d -glucose integrated with computed tomography (CT), ( 18 F-FDG PET/CT), has recently improved the mediastinal nodal staging of non-small cell lung cancer (NSCLC), this method can show false negativity. We immunohistochemically investigated the expression of glucose transporters (GLUT-1, SGLT-1, and SGLT-2) in false negative and true positive mediastinal nodes via 18 F-FDG PET/CT. Methods: We investigated patients with clinically-diagnosed N0/pathological N2 diseases and patients with clinically-diagnosed N2/pathological N2 disease. The patients who were included in this study were evaluated using 18 F-FDG PET/CT followed by surgical resection between January 2004 and December 2015. The expression of GLUT-1, SGLT-1, and SGLT-2 in the metastatic mediastinal lymph nodes, and clinicopathological variables such as primary tumor size, lymph node size, histological type, and SUVmax of the primary lesion, were compared between false negative nodes and true positive nodes. Results: The total number of PET false negative metastatic mediastinal lymph nodes was 22 in the 17 patients who were clinical N0/pathological N2, and the number of PET true positives was 15 in the 11 patients who were clinical N2/pathological N2. GLUT-1 expression was positive in five false negative nodes and 10 true positive nodes. SGLT-2 expression was positive in 12 false negative nodes and one true positive node, whereas both false negative and true positive nodes showed no SGLT-1 staining. Univariate analysis showed that the reduced expression of GLUT-1 (P = 0.015), and overexpression of SGLT-2 (P = 0.004) were the significant causative factors for false negative nodes. Multivariate analysis also showed that the reduced expression of GLUT-1 (P = 0.012) and overexpression of SGLT-2 (P = 0.006) were the significant causative factors for false negative nodes. Conclusion: It suggests that the reduced expression of GLUT-1 and overexpression of SGLT-2 are associated with false-negative lymph node metastases in NSCLC.